THE FINANCIAL EFFECTS OF THE FISCAL SOVEREIGNTY OF MUNICIPALITY REGARDING REAL ESTATE TAX - Agnieszka Żołądkiewicz-Kuzioła (Copernican Journal of Finance & Accounting, 2023)
The aim of the article is to identify the differentiation of the financial effects of a municipality’s fiscal sovereignty in the field of real estate tax from the point of view of such criteria as the type of municipality (rural, urban, urban-rural and town with poviat rights) and the type of fiscal sovereignty instrument (tax rates lower than the maximum, reliefs and exemptions, redemption of tax arrears, payment in instalments, deferral of the payment date). The research covering the years 2017–2021 was based on data from the Ministry of Finance. Based on the research, it was shown that the effects of fiscal sovereignty were the most significant in rural municipalities, while the smallest in towns with poviat rights. All types of municipalities used common instruments, such as e.g., the lowering of tax rates, to a greater extent than the discretionary instruments resulting from the Tax Ordinance.